The class of COVID-19: Changes to the monitoring of the structure and case mix for physiotherapy clinical placements - Andrea H Hams; Taryn L Jones (Bond University, 2022)
_Background_: Physiotherapy students spend approximately 1,000 hours outside of the university completing clinical placements, yet little attention has been devoted to the objective evaluation of the clinical placement experience and the client case-mix managed by students. _Summary_: In this case description, the implementation of a clinical portfolio in response to the COVID-19 pandemic to objectively monitor physiotherapy students' clinical education experience is analysed. In addition, insight into the clinical placement variations that have necessitated the implementation of the clinical portfolio is provided. The potential impact of these changes on new graduate recruitment is also discussed and recommendations regarding the implementation of a clinical portfolio as common practice moving forward are provided. Future research is outlined that will ensure continued evaluation of the impact of the COVID-19 pandemic on physiotherapy clinical placements both during and after the pandemic. _Conclusions_: The primary reason for the implementation of a clinical portfolio was to improve physiotherapy clinical placement monitoring during the COVID-19 pandemic and to support meeting the profession's rigorous accreditation requirements. The clinical portfolio design was practical in that it was online and flexible and had no direct financial cost to set up. The tracking of learning experience through a clinical portfolio recognises the breadth and variability of experience gained by students whilst on clinical placement. In addition to the refinement of clinical experience tracking, there was anecdotal reporting of improved student-clinical academic communication regarding their learning opportunities.